Detection of Egg Diameters and Hatching Rates of California, China, Utah, and Vietnam Originated Artemia sp. in Different Temperatures and Salinity - YÜRÜTEN ÖZDEMİR, Keriman (Alinteri Zirai Bilimler Dergisi, 2018)
In this study number of eggs in 1 gram, egg diameters and hatching rates in 25oC and 30oC temperatures and 25‰, 030‰, 035‰ salinity of Artemia sp. from four different origins were analyzed. Egg count and diameter measurement was carried out with the use of binocular microscope. The most number of eggs in 1 gram was determined to be from Utah originated Artemia sp. while the least was determined to be from California originated ones. Hatching rates were detected to be the highest at 30oC temperature, 25‰ salinity, at the 18th hour in Vietnam originated Artemia sp. In conclusion, it was detected that the hatching time for Artemia sp. varies depending on the temperature and salinity of the water.
Keywords: Artemia sp.; Egg Diameter; Hatching Rate